Credit access and borrowing costs in Poland's agricultural credit market: a hedonic pricing approach - Martin Petrick; Laure Latruffe (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2003)
The paper empirically investigates credit access and borrowing costs in Poland's rural financial market. We conduct an econometric analysis based on cross-sectional survey data including formal loans taken in the period 1997-1999. A hedonic regression of the effective interest rate, comprising both the nominal interest rate and additional transaction costs faced by farmers, allows the identification of the determinants of borrowing costs. These determinants can be interpreted as loan attributes and their implicit prices calculated. We proceed in two steps. In the first step, farmers' credit access is estimated by a Probit model. The second step is the hedonic regression, in which the Probit results are taken to test for selectivity. The results support the widely held view that formal lenders tend to discriminate against smaller farms. They also suggest that the presence of devices to screen and signal the quality of borrowers makes borrowing more likely and reduces borrowing costs. Furthermore, the analysis reveals that the choice of the type of bank has a significant effect on borrowing costs. All other loan attributes equal, the traditional institutions for agricultural lending (the cooperative banks and the governmentally controlled Bank for Food Economy) offer between 1.1 and 1.3 percentage point higher effective interest rates as compared with the most favourable terms available, which has implications for a potential future restructuring of the Polish rural banking sector. In addition, there is strong evidence that the government subsidisation of nominal interest rates is severely counteracted by increased transaction costs and an adverse selection of borrowers. However, there is still a net reduction of the effective interest rate by 1.4 percentage point on average, compared to non-subsidised loans. This raises the question whether lending procedures under the government programme are sufficiently streamlined and whether loans are effectively targeted. – – Gegenstand dieses Beitrags ist die empirische Untersuchung von Kreditzugang und Kreditkosten auf Polens ländlichen Finanzmärkten. Zu diesem Zweck wird eine ökonometrische Analyse von Querschnittsdaten durchgeführt, die Informationen zu formellen Kreditkontrakten für die Zeitperiode 1997-1999 beinhaltet. Mit Hilfe einer hedonischen Regression des effektiven Zinssatzes, der sowohl den nominalen Zinssatz als auch zusätzliche Transaktionskosten umfasst, werden die Determinanten der Kreditkosten analysiert. Diese Determinanten können als Krediteigenschaften interpretiert werden, was eine Berechnung ihrer impliziten Preise ermöglicht. Unser Vorgehen besteht aus zwei Schritten. Im ersten Schritt wird der Zugang zu Krediten durch ein Probit-Modell geschätzt. Der zweite Schritt beinhaltet die hedonische Regression, wobei die Probit-Ergebnisse für einen Selektivitäts-Test verwendet werden. Die Ergebnisse bestätigen die verbreitete Ansicht, dass formelle Kreditgeber kleinere landwirtschaftliche Betriebe tendenziell benachteiligen. Die Ergebnisse legen außerdem nahe, dass Verfahren zur Aufdeckung und Signalisierung der Nachfragerqualitäten die Kreditaufnahme wahrscheinlicher machen und die Kreditkosten senken. Die Analyse verdeutlicht, dass die Wahl der Bank einen signifikanten Effekt auf die Höhe der Kreditkosten hat. Bei sonst gleichen Vertragseigenschaften bieten die traditionellen landwirtschaftlichen Kreditgeber (die Genossenschaftsbanken und die von der Regierung kontrollierte Bank für Nahrungsmittelwirtschaft) um 1,1 bzw. 1,3 Prozentpunkte höhere effektive Zinssätze, verglichen mit dem günstigsten Angebot. Dies ist für eine künftige Restrukturierung des ländlichen Bankensektors in Polen von Bedeutung. Außerdem gibt es deutliche Hinweise darauf, dass die Wirkung der staatlichen Zinssubventionierung durch gesteigerte Transaktionskosten und adverse Selektion von Kreditnehmern stark verringert wird. Allerdings führt sie im Vergleich zu nichtsubventionierten Krediten immer noch zu einer Netto-Verringerung des effektiven Zinssatzes um durchschnittlich 1,4 Prozentpunkte. Es stellt sich daher die Frage, ob die Vergabeprozeduren des staatlichen Kreditprogramms hinreichend effizient sind und ob die Kredite effektiv plaziert werden.
urn:nbn:de:gbv:3:2-23217
Keywords: Q12; Q14; P32; 330; agricultural finance; credit policy; transaction costs; Poland; microeconometrics; Agrarfinanzierung; Kreditpolitik; Transaktionskosten; Polen; Mikroökonometrie; Agrarkredit; Ländlicher Finanzmarkt; Zins; Hedonischer Preis; Kapitalkosten; Transaktionskosten; Schätzung; Polen